Effect of gender participation on determining the maturity of crossed-due loans: Evidence from microfinance companies of Nepal - Arjun Kumar Dahal; Ganesh Bhattarai; Prem Bahadur Budhathoki (Banks and Bank Systems, 2023)
The impact of gender participation on the maturity of crossed-due loans is observed in this study. Furthermore, the associations between maturity of crossed-due loans, their number, and loan issued on physical collateral and collective bail are also monitored using the unbalanced panel data of thirty microfinance companies. The study investigates the short- and long-term link between response and predictor variables. It is founded on an exploratory and descriptive research design. The Hausman test, fixed effect or LSDV model, Pedroni and Kao co-integration test are used to observe the relation and impact. The maturity crossed due loan number, total loan amount, loan issued against physical collateral, and loan allocated on collective bail are jointly significant to determine the maturity of crossed due loan amount of microfinance companies of Nepal. It is found that women are more conscientious in repaying loans on time compared to male borrowers. Per rupee 0.382 rupees, a maturity crossed due loan is found in microfinance companies where only women can borrow, but per rupee 0.404 rupees, a time crossed due loan is found where men and women can borrow. Policymakers of banks are not necessarily hesitant to provide loans to female borrowers.